2017
DOI: 10.1002/ets2.12159
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Levels of Performance Feedback on TOEFL iBT® Reading Practice Test Performance

Abstract: College Board is composed of schools, colleges, school systems, and educational associations; GRE Board members are associated with graduate education. The test is now wholly owned and operated by ETS.ETS administers the TOEFL program under the general direction of a policy board that was established by, and is affiliated with, the sponsoring organizations. Members of the TOEFL Board (previously the Policy Council) represent the College Board, the GRE Board, and such institutions and agencies as graduate schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Ellis argues that using focused tasks goes hand in hand with intensive feedback in developing a specified set of language features and skills. The findings also echo those by Sawaki (2017), who found that the provision of feedback affected the degree to which the participants perceived the benefits of the study materials to understanding different item types and developing strategies for mastering the sub-skills within a short time. Similar to the guidelines set by Sawaki, three levels of verified and elaborated feedback were provided to the participants upon completion of the listening and reading exercises: (a) feedback on the correctness of learner response (knowledge of the correct answers), (b) feedback and rationales for correct/incorrect answers were discussed during the training sessions, and (c) feedback and the rationales of listening and reading activities covering the sub-skills tested with on-demand video lectures on the skills that needed focused attention and effort.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Ellis argues that using focused tasks goes hand in hand with intensive feedback in developing a specified set of language features and skills. The findings also echo those by Sawaki (2017), who found that the provision of feedback affected the degree to which the participants perceived the benefits of the study materials to understanding different item types and developing strategies for mastering the sub-skills within a short time. Similar to the guidelines set by Sawaki, three levels of verified and elaborated feedback were provided to the participants upon completion of the listening and reading exercises: (a) feedback on the correctness of learner response (knowledge of the correct answers), (b) feedback and rationales for correct/incorrect answers were discussed during the training sessions, and (c) feedback and the rationales of listening and reading activities covering the sub-skills tested with on-demand video lectures on the skills that needed focused attention and effort.…”
Section: Discussionsupporting
confidence: 80%
“…Inadequate language learning and teaching activities are partly responsible for students' lack of language ability, as research in English as a Foreign Language (EFL) suggests. For instance, while answering reading comprehension questions, Sawaki (2017) found that when students spent too much time on the initial text reading, they had a fragmented understanding of the global text structure. Therefore, they found it difficult to quickly locate specific information or identify main ideas and essential details.…”
Section: Listening and Reading Comprehensionmentioning
confidence: 99%
See 3 more Smart Citations